Output-Based Health Care : Paying for Performance in Haiti - Eichler, Rena; Auxila, Paul; Pollock, John (World Bank, Washington, DC, 2012)
In 1999 the U.S. Agency for International Development introduced performance-based contracting in an effort to improve the effectiveness of some of Haiti's nongovernmental organizations in providing basic health services, such as immunization and prenatal and maternal care. These providers has been operating under a payment system that reimbursed their expenses up to a ceiling. The new systems set performance targets and withheld a portion of their historical budget, allowing them to earn back the withheld payment plus a bonus if they met the targets. A one-year pilot involving three providers showed some marked improvements in performance.